Performance evaluation of an optimized reciprocating shaker with PID control and Arduino technology: driving circular economy in laboratory equipment - Achuy Flores, Ana Sofía (2025)
The COVID-19 pandemic has accelerated the transition to virtual education and self-directed learning, highlighting the need for practical and affordable educational tools. This study addresses the remanufacturing of an old reciprocating shaker using a PID control system based on the Ziegler-Nichols method and Arduino technology. The¡ equipment was evaluated under various load and speed conditions, achieving precise agitation control with a minimum percentage error of 3%. The results demonstrate the effectiveness of PID control in stabilizing motor speed within the range of 150 to 250 RPM, with an average stabilization time of 2 seconds. Additionally, electrical measurements validated the efficiency of the alternating current regulator, while the reuse of components underscores the viability of integrating circular economy practices into education. This research offers an economically and environmentally sustainable solution for the manufacturing of laboratory equipment, fostering innovation in the teaching of experimental sciences.